The Role Of Financial Literacy On Financial Management Of Micro, Small And Medium Enterprises In North Kolaka Regency - Risnawati; Erwina (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to analyze the influence of financial literacy on the financial management of Micro, Small, and Medium Enterprises (MSMEs) in North Kolaka Regency. MSMEs play a strategic role in the Indonesian economy; however, many business actors still face fundamental challenges in managing their finances due to limited financial knowledge and skills. This research adopts a quantitative approach with a sample of 100 MSME owners selected using incidental sampling techniques. Primary data were collected through structured questionnaires, supported by observations and brief interviews to enrich contextual understanding. The financial literacy variable was measured through indicators of financial knowledge, attitudes, and behavior, while financial management was assessed through practices of financial recording, budgeting, cash flow management, and the use of simple financial tools. The data were analyzed using simple linear regression to test the effect of financial literacy on financial management. The results show that financial literacy has a positive and significant effect on the financial management of MSMEs in North Kolaka Regency, as indicated by a significance value of 0.002 (< 0.05) and a positive regression coefficient. These findings imply that higher levels of financial literacy enable MSME actors to manage their finances more effectively, including separating personal and business finances, planning budgets, and maintaining business cash flow stability. The study suggests the importance of strengthening financial education programs and mentoring for MSMEs as a strategic step to improve business sustainability and regional economic resilience.